An Unusual Occurrence of Hepatic Granulomas and Secondary Sitosterolemia in Turner Syndrome - JayaKrishna Chintanaboina; Pragnesh R. Shah; Thomas R. Riley (Case Reports in Medicine)
Although abnormal liver function tests occur in 50–80% of cases with Turner syndrome, there are no previous reports of overt hepatic disease or hepatic granulomas associated with Turner’s syndrome. We report three cases of Turner syndrome associated with hepatic granulomas with a wide range of liver dysfunction. Of the three patients, first patient underwent liver transplantation; second patient remained stable on immunosuppressants; and third patient died from complications of decompensated liver cirrhosis as she declined liver transplantation due to multiple comorbidities. One patient had sitosterolemia, a rare inherited autosomal recessive disorder of cholesterol metabolism, after she ingested β-sitosterol supplement and had worsening liver function tests and lipid panel. She had remarkably abnormal lipid panel that responded to ezetimibe and by stopping the β-sitosterol supplement.